IS GOJEK DRIVERALREADY PROSPEROUS BY MAQASID SYARIAH? - Anita Rahmawaty; Kharis Fadlullah Hana; Aryanti Muhtar Kusuma; Anggie Nurulita (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2021)
This study aims to analyze the welfare of Millenial Gojek driver in Kudus district from the perspective of maqashid sharia. This research is field research using a qualitative approach. Research data were collected through interviews, observation, and documentation. Informants in this study are Millenial Gojek drivers who operate in Kudus district and have joined as Gojek partners for at least four months. The results showed that first, Millenial Gojek drivers in Kudus district have not fully achieved maslahah welfare. This is because the needs for dharuriyat has not been fully met, namely 5 research indicators among others hifdz al-din, hifdz al-nafs, hifdz al-aql, hifdz al-nasl, dan hifdz al-mal. Second, the hajiyat needs of informants have been met, namely having a motorbike and smartphone. Third, tahsaniyat needs of the informants have not been fulfilled, namely health insurance.